If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8ln(x + -5) = 12 Reorder the terms: 8ln(-5 + x) = 12 (-5 * 8ln + x * 8ln) = 12 (-40ln + 8lnx) = 12 Solving -40ln + 8lnx = 12 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Reorder the terms: -12 + -40ln + 8lnx = 12 + -12 Combine like terms: 12 + -12 = 0 -12 + -40ln + 8lnx = 0 Factor out the Greatest Common Factor (GCF), '4'. 4(-3 + -10ln + 2lnx) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(-3 + -10ln + 2lnx)' equal to zero and attempt to solve: Simplifying -3 + -10ln + 2lnx = 0 Solving -3 + -10ln + 2lnx = 0 Move all terms containing l to the left, all other terms to the right. Add '3' to each side of the equation. -3 + -10ln + 3 + 2lnx = 0 + 3 Reorder the terms: -3 + 3 + -10ln + 2lnx = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -10ln + 2lnx = 0 + 3 -10ln + 2lnx = 0 + 3 Combine like terms: 0 + 3 = 3 -10ln + 2lnx = 3 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 6x+7y-32=-12 | | 2x^3-6x+6=0 | | tan(51)=25/x | | 5x+6y+42=10 | | 10[x]= | | 120x+56y=498 | | .5x-1.5=0 | | 13y-39= | | 2x(3x+4)=6x+8 | | (X)=x(x+7) | | 8x+3=23+4x | | 4ln(x-5)=3 | | x^2+6x+27=22 | | 9x+5=40+4x | | x^2+6x+27=66 | | 8x+3=-45+2x | | 5x+3=-11+3x | | F(x)=x(x+7) | | 6x+3=-29+2x | | 8x=8x-3 | | 5x+19=73-4x | | 2m+5=-8m+4 | | 3x+7=31-5x | | 3x+12=92-7x | | 3(2x+1)=-2(3x-2) | | 8p^2-9=-59 | | 3(3x+4)=9 | | 9p^2+18p-61=-6 | | sin(3x+2)=cos(10-4x) | | 4x^2-2x+10=0 | | 6x+18=68-4x | | 5+(x+2)=(4x+1) |